Biopesticidal effect of botanicals on the management of mustard diseases - YADAV*, M.S. (Indian Phytopathology, 2009)
Plant extracts (1%) of five botanicals viz., Allium sativum, A. cepa, Azardirachta indica, Calotropis procera and Eucalyptus globosus were tested for their biopesticidal activity on mustard diseases. Mancozeb, effective in management of mustard diseases was included as standard check. All the botanicals were found significantly superior to control. A. sativum (garlic) and Eucalyptus were found more effective than Calotropis (aak) and Azardirachta indica (neem). Two years pooled data reveals that three sprays of A. sativum bulb extract at 15 days interval gives the minimum disease indices of white rust (39.5%) and Alternaria blight (43.3%) on leaf and minimum incidence of Sclerotinia rot (1.7%) on stem in comparison to control (respective values of 66.2, 56.6 and 2.9 % for white rust, Alternaria blight & Sclerotinia rot). Seed yield in garlic (1171 kg/ ha) increased significantly in comparison to control (885.3 kg/ha) and was at par with mancozeb and neem (1307.2 & 1209.5 kg/ha). The results proved that application of A. sativum could be biopesticidal and ecofriendly, substitute for chemical fungicide, mancozeb in management of mustard diseases.